Design of a Photoelectric Measuring Robot for Straightness of Deep/Blind Hole with Automatic Centering Function - Zhao, Haifeng (Manufacturing Technology Journal, 2023)
In order to quickly measure the straightness parameters of the deep hole/blind hole axis, a robot for measuring the straightness of the deep hole/blind hole axis based on the photoelectric prin-ciple is designed. Using the linearity of the laser as a reference, the straightness of the inner hole can be detected through the function that the PSD sensor can accurately locate the position of the energy center of the light. By studying the relationship between the position of the light spot and the output voltage of the PSD device, the measurement model of the straightness of the deep hole axis is derived. During the measurement, the robot spiral driving mechanism moves back and forth inside the deep/blind hole, and the automatic centering mechanism realizes the precise positioning of the deep/blind hole axis. The laser fixed on the axis of the automatic centering mechanism can illuminate the PSD target to obtain the current position data of the deep/blind hole axis. Use the least square median method to eliminate the gross error of the obtained data, and the least square principle fitting can obtain the measurement results of the current axis straightness. In order to ensure the measurement accuracy, the measuring robot is calibrated by a standard ring gauge and used for the age of the pipe with an inner diameter of 135mm to obtain an error accuracy of less than 0.05 mm for the axis.
Keywords: Deep/blind hole; Straightness; Photoelectric measurement; Self-centering device; Position sensitive detector